Risk measurement and monitoring - Grima, Simon; Torre-Enciso, María Isabel Martínez; Castelli, Maurizio (Emerald Publishing Limited, 2025)
The need to manage risk is increasingly featured in legislation and regulations. Simultaneously the need to integrate risk management into general management practices of organisations is fast becoming a key objective for all stakeholders. In addition, the drive to improve corporate governance is compelling organisations to examine the manner in which they manage risks and operational and strategic levels The third volume of The FERMA-rimap Series defines approaches to modelling uncertainty and helps readers distinguish between simple, complex and matrix organisational structures, and explores operational risk management. All risk professionals have a duty to remain updated with the evolution of the risk landscape. The FERMA-rimap Series serves as a proactive, continuous and dynamic learning and research platform to respond to risk managers' present and future educational and professional needs. The volumes set crucial standard taxonomy for European Risk Professionals and an essential reading for students aspiring to gain a qualification in Risk Management.
Keywords: Risk management.; Business & Economics -- Insurance -- Risk Assessment & Management.; Business strategy.; Insurance and actuarial studies.; Risk assessment.; elektronické knihy; electronic books